Stutter, houwer, vliegenier. Sociaal-professioneel profiel van tewerkgestelden in de Willem-Sophia, 1945-1946 - Schoot Uiterkamp, Annet (Studies over de sociaaleconomische geschiedenis van Limburg, 2018)
Timberman, hewer, aviator. The socio-professional profile of political prisoners at the mine Willem-Sophia, 1945-1946 This article is a sequel to ‘“For the time being keep it silent”. Employment of political prisoners at the mine Willem-Sophia in Spekholzerheide (1945-1946)’ in Jaarboek 2017. It outlines the profile of the first political prisoners employed in this mine. The data are extracted from two registers that include personal and professional particulars of the 641 employees concerned. It surveys former employer or profession, place of origin, age, duration of employment and reason of dismissal of the political prisoners in comparison with the ‘free’ miners. The detention grounds are discussed and illustrated by some case histories. Apart from their political collaboration there seems to be no remarkable differences between this group of ‘infected’ miners and their ‘free’ colleagues.